THE STRATEGIC DYNAMICS OF AN AGRICULTURAL COOPERATIVE: FROM ORGANIZATIONAL MODERNIZATION FOCUSED ON PRODUCTION ACTIVITIES TO THE CONSOLIDATION OF AN IMPORTANT PRODUCTION AND SERVICES LATINAMERICAN POLE CONCERNED WITH THE FLOWER AGRIBUSINESS - Marly Cavalcanti (FATEC-SP) (International Journal of Research Science and Management, 2016)
This work presents an analytical study on the strategic evolution adopted by Holambra Agricultural Cooperative (CAPH) along its history, going from strictly organizational aspects up to the structuring of the Holambra municipality. A methodological option for qualitative analysis was the approach of a case study [26]. The consolidation of the importance of the services sector for the municipality of Holambra is characterized by the increasing force of tourism (businesses or leisure), mainly related to flower businesses, with a small parcel concerned with the peculiar aspects of the Dutch culture.